Creating incentives to avoid deforestation (The Office [Georgetown]GY, 2009)
Analyzes what will be required to align the economic interests of tropical forest countries with those of the broader community. Sets out two foundational concepts - Economic Value to the Nation (EVN) and Economic Value to the World (EVW) - that bound the solution space for avoiding deforestation. Describes an approach for calculating EVN and uses Guyana as a case study. Discusses implications for designing a mechanism to reduce emission from deforestation.
Bibliography: p. 32